THE EFFECT OF ADVERTISING, CELEBRITY ENDORSER, AND BRAND AWARENESS ON PURCHASE DECISION - Kusumah Wardani, Rahayu; Sukaris, Sukaris (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2021)
Currently, the number of internet users in Indonesia has increased significantly. In 2019-2020 as many as 196.7 million people, and in 2021 it will increase to approximately 25.5 million internet users. Internet technology is also used as an e-commerce trade transaction. A survey conducted by Katadata shows that 88.1% of internet users in Indonesia use e-commerce services. This number is the highest presentation in the world in April 2021. One of the most accessed e-commerce shopping sites is Shopee, with an average monthly visit of 93.4 million. There are several factors that can cause someone to decide to buy online on e-commerce, including television media advertisements, social media advertisements, celebrity endorsers, and brand awareness. This study aims to determine the effect of advertising, celebrity endorser and brand awareness in purchasing decisions on the shopee shopping application. The population of this research is the students of the Faculty of Economics and Business, University of Muhammadiyah Gresik. Samples were taken of as many as 100 students who had made a purchase transaction at shopee. Data was taken using a questionnaire whose measurement was using a likert scale. The data obtained were processed and analyzed using multiple linear regression analysis techniques, while the hypothesis testing used a partial test or t test.